2021
DOI: 10.1002/ange.202110749
|View full text |Cite
|
Sign up to set email alerts
|

An N‐Trifluoromethylation/Cyclization Strategy for Accessing Diverse N‐Trifluoromethyl Azoles from Nitriles and 1,3‐Dipoles

Abstract: N-Trifluoromethyl azoles are valuable targets in medicinal chemistry,b ut their synthesis is challenging.C lassical preparation of N-CF 3 azoles relies on the functional group interconversions but suffers from tedious N-pre-functionalization and unfriendly agents.I ntroduction of the CF 3 onto the nitrogen of heterocycles provides adirect route to such motifs, but the N-trifluoromethylation remains underdeveloped. Reported here is an alternative and scalable cyclization strategy based on NCF 3 -containing synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Xu, Guan, and Wang et al [ 80 ] reported an alternative and scalable cyclization strategy based on N -CF 3 -containing synthons for constructing diverse N -CF 3 azoles, including N -CF 3 tetrazoles, N -CF 3 imidazoles, and N -CF 3 1,2,3-triazoles ( Scheme 13 ). This method involved using a hypervalent iodine reagent for trifluoromethylation in combination with a base to efficiently carry out the reaction.…”
Section: Five-membered Heterocyclesmentioning
confidence: 99%
“…Xu, Guan, and Wang et al [ 80 ] reported an alternative and scalable cyclization strategy based on N -CF 3 -containing synthons for constructing diverse N -CF 3 azoles, including N -CF 3 tetrazoles, N -CF 3 imidazoles, and N -CF 3 1,2,3-triazoles ( Scheme 13 ). This method involved using a hypervalent iodine reagent for trifluoromethylation in combination with a base to efficiently carry out the reaction.…”
Section: Five-membered Heterocyclesmentioning
confidence: 99%
“…During our ongoing explorations in the field of trifluoromethylation, an externally coordinated CF 3 -containing λ 3 -iodane (PhICF 3 Cl) 8 was synthesized to be used in a set of trifluoromethylation reactions. 9 Efficient trifluoromethylative bifunctionalization reactions of alkenes have been developed by our group recently. 9 a – d In order to extend the synthetic applications of PhICF 3 Cl, the trifluoromethylation of alkynes was investigated in the follow-up work.…”
Section: Introductionmentioning
confidence: 99%
“…1 a–c ,2 In addition to the typical methods which relied on the functional group interconversions with tedious N -prefunctionalizations and the emerging N -CF 3 synthon approaches, 6,7 several elegant works have been reported to achieve direct electrophilic N -trifluoromethylations (Scheme 1b). 8 Recently, Bolm et al and Selander et al have accomplished a transition metal (TM)-mediated radical N -trifluoromethylation of sulfoximines and aryl nitroso derivatives, respectively. 9 However, it is still highly desirable to develop efficient approaches for the formation of N -CF 3 bonds to access structurally diverse heterocyclic scaffolds.…”
Section: Introductionmentioning
confidence: 99%